Between the stage and behind the scenes: accounts of an educational and artistic experience. (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2025)
This article presents an experience report that combines didactic and artistic experience, based on an updated excerpt from the research entitled “The dramaturgical meaning of the characterization of the performer's body: a case study of the shows Gota D'Água and O Abajur Lilás.” The main objective is to understand the relationship between characterization and the actor/performer's body. The narrative is constructed from a critical reflection on the experiences lived during the artistic process, supported by an empirical approach. In addition, the theoretical and analytical references used contribute to a deeper understanding of this relationship, highlighting the importance of the body in the construction of the character, as well as in the development of the creative and aesthetic theatrical process.
Keywords: characterization; body; costume; creative process